Measuring the Company’s Capabilities and Assessing their Impact on Its Economic Results: Analytic Tools - E. P. Tretiakova; M. S. Tretiakova (Управленческие науки)
With the increasing uncertainty of the external environment, the capabilities of companies become the driving force behind their operations and development, making the management of these capabilities an important task for management. The aim of the research is to develop a toolkit for measuring a company’s capabilities, assessing their condition, and evaluating their impact on productivity. The author’s concept is presented, according to which the final results of the company’s activity are formed through the mechanism of interaction of the company’s organizational capability with acquired resources, the formation of resource capabilities (production, financial, labor, and market) and their transformation into tangible and intangible products. Based on this model, methodological guidelines have been developed for measuring the capabilities of organizations and assessing their impact on the final results, a value-functional approach to selecting appropriate indicators, and analytical tools. The following methods have been substantiated: modeling, the indicator method, data convolution, scaling, and statistical methods. To measure capabilities, it is proposed to use indicators aggregated into composite indices through a developed algorithm. The use of sales growth rate, market capitalization, profit before taxes, and net cash flow as the final results of the company (productivity indicators) has been justified. To solve analytical tasks at different levels of management, combinations of methods, tools and indicators called “research formats” (detailed, diagnostic, express diagnostic analysis) were developed. The results of the empirical testing of the author’s research are presented: through detailed analysis, the validity of the proposed approach and tools has been established, and through diagnostic analysis, the stability of the selected indicators and constructed mathematical models beyond the observation period was identified. The result is a toolkit for researching crucial company’s capabilities, enabling management to analyze and monitor these capabilities, assess their productivity, make forecasts of productivity indicators, and develop a system for managing the organization’s capabilities.